2022
DOI: 10.31083/j.jomh1810201
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Protein Influences Expression of ICOSL and ICAM-2 in Prostate Cancer

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the novel coronavirus responsible for the COVID-19 pandemic. The viral protein of SARS-CoV-2, spike protein (SP), mediates entry into host cells, contributing to pathogenesis of COVID-19. Prostate cancer is the most common cancer among men in the United States. Inducible T-cell costimulator ligand (ICOSL) and intercellular cell adhesion molecule 2 (ICAM-2) are expressed in cancer cells and their roles in cancer growth remain controvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…We further expanded our study to investigate if SARS-CoV-2 spike protein has any effect on expression of costimulatory molecules. To our surprise, it was found that SARS-CoV-2 spike protein caused a downregulation of ICAM-2 but an upregulation of ICOSL [8]. Our studies suggest that SARS-CoV-2 spike protein may not only inhibit growth of prostate cancer, but also modulate the expression levels of costimulatory molecules which are critical for immune response.…”
Section: Letter To the Editormentioning
confidence: 62%
“…We further expanded our study to investigate if SARS-CoV-2 spike protein has any effect on expression of costimulatory molecules. To our surprise, it was found that SARS-CoV-2 spike protein caused a downregulation of ICAM-2 but an upregulation of ICOSL [8]. Our studies suggest that SARS-CoV-2 spike protein may not only inhibit growth of prostate cancer, but also modulate the expression levels of costimulatory molecules which are critical for immune response.…”
Section: Letter To the Editormentioning
confidence: 62%